Design and Development of a DAST Based on 2RPS-1S Parallel Mechanism - Abdullah, Fahisal; Munaaim, M. Arkam C.; Azalan, Mohd Shuhanaz Zanar; Othman, Siti Marhainis (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
There are a number of process design that available in the literature in order to develop a new parallel mechanism that can be applied to the solar farm. However, the best ways to develop a new mechanism still have a challenge. Therefore, this project provides a systematic process design with include the kinematics derivation, mechanical and hardware development, and software development. This project aims to design and development of a Dual Axes Solar Tracking (DAST) based on 2RPS (Revolute-Prismatic-Spherical) -1S (Spherical) parallel mechanism by implementing the systematic process design. The focus is on a two degree-of-freedom (DOF) parallel mechanism – which encloses a closed loop in the structure. Based on MATLAB simulation and real prototyping motion result is show that the movement position of the solar panel has similarity. In summary, both method simulation and prototyping are able to represent a two DOF parallel mechanism. At the same time, the comparative analysis is able also to validate the equation of kinematics that derives from Denavit-Harternberg (DH) methods.